The Influence of Building Independence and Morals on Increasing the Capacity Building of Inmates at the Class IIA Bulukumba Prison - Nurfitriani Burhan; Muhammad Yusuf; Nurinaya, Nurinaya (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine the effect of fostering independence and moral development on increasing the capacity building of residents assisted by the Bulukumba Class IIA Correctional Institution. The type of data used in this research is quantitative data obtained from questionnaires distributed and related to the problem studied. Data collection techniques were carried out using observation and distributing questionnaires. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research used the Likert scale method. Based on the results of data research using statistical calculations through the Statistical for the Social Science (SPSS) version 21 application regarding the influence of fostering independence and moral development on increasing the capacity building of residents assisted by the Bulukumba Class IIA Penitentiary. which has been discussed in the previous chapter, the author draws a conclusion, namely that the development of independence and the development of morals have a positive and significant effect on increasing the capacity building of the inmates of the Bulukumba Class IIA Penitentiary as evidenced by the regression coefficient for the development of independence of 0.212 and a thiung value of 4.965 > ttable 1.990 with significance value 0.000 <0.05. Meanwhile, the regression coefficient for moral development is 0.354 and the thiung value is 11,210 > ttable 1.990 with a significance value of 0.000 < 0.05 .